Comparison of the Interference Effects on Somatosensory Evoked Potential from Tonic, Burst, and High-dose Spinal Cord Stimulations - Eiichirou URASAKI; Yasushi MIYAGI; Shogo MURAMATSU; Yasutaka EZAKI (Neurologia Medico-Chirurgica, 2022)
Spinal cord stimulations have been used widely to treat intractable neuropathic pain. The conventional spinal cord stimulation paradigm, the “tonic” type, suppresses excessive activation of wide dynamic range neurons in the dorsal horn via the collateral branch from the dorsal column. Therefore, preserved dorsal column function is an important prerequisite for tonic spinal cord stimulations. A tonic spinal cord stimulation requires eliciting paresthesia in the painful area due to stimulation of the dorsal column and dorsal root. Recent spinal cord stimulation paradigms, including burst and high-dose, are set below the paresthesia threshold and are proposed to have different pain reduction mechanisms. We conducted an interference study of these different stimulation paradigms on the somatosensory evoked potential (SEP) to investigate differences in the sites of action between tonic and new spinal cord stimulations. We recorded posterior tibial nerve-stimulated SEP in seven patients with neuropathic pain during tonic, burst, and high-dose stimulations. The total electrical energy delivered was calculated during SEP-spinal cord stimulation interference studies. High-dose stimulations could not reduce the SEP amplitude despite higher energy delivery than tonic stimulation. Burst stimulation with an energy similar to the tonic stimulation could not reduce SEP amplitude as tonic stimulation. The study results suggested different sites of action and effects on the spinal cord between the conventional tonic and burst or high-dose spinal cord stimulations.